2008
DOI: 10.1200/jco.2008.16.2727
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Analysis of the Effect of Age on Adjuvant Cisplatin-Based Chemotherapy for Completely Resected Non–Small-Cell Lung Cancer

Abstract: Adjuvant cisplatin-based chemotherapy should not be withheld from elderly patients with NSCLC purely on the basis of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(103 citation statements)
references
References 30 publications
6
90
3
3
Order By: Relevance
“…Fruh et al analyzed the effects of age on cisplatin-based adjuvant chemotherapy using patient-level data from the Lung Adjuvant Cisplatin Evaluation (LACE) meta-analysis. 26 In this analysis, they found that older patients (70 years) received lower total cisplatin doses compared with younger patients (<65 years) and those considered to be in the middle age category (65-69 years). They found that there were no significant differences in either OS or event-free survival among the 3 age groups studied.…”
Section: Discussionmentioning
confidence: 79%
“…Fruh et al analyzed the effects of age on cisplatin-based adjuvant chemotherapy using patient-level data from the Lung Adjuvant Cisplatin Evaluation (LACE) meta-analysis. 26 In this analysis, they found that older patients (70 years) received lower total cisplatin doses compared with younger patients (<65 years) and those considered to be in the middle age category (65-69 years). They found that there were no significant differences in either OS or event-free survival among the 3 age groups studied.…”
Section: Discussionmentioning
confidence: 79%
“…Adjuvant chemotherapies have increased survival rates by approximately 5% in 5 years in NSCLC, which does not appear to be satisfactory (3,9). Severe toxicities are occasionally observed in patients treated with CDDP-based chemotherapies, and chemotherapy-related death has been one of the major problems with adjuvant chemotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that many factors can affect the efficacy and outcome of post-operative chemotherapy with the NP regimen (Früh et al, 2008). We stratified the patients and found that patients with NSCLC at <55 years of age, with squamous carcinoma at stage I, survived significantly longer than those at older age, with adenocarcinoma or stage II or IIIA.…”
Section: Discussionmentioning
confidence: 91%